Analisis Pengaruh Kepuasan Kerja terhadap Intensi Turnover pada Tenaga Pengajar di SMA Mekarwangi Lembang - Anang Sanjaya; Ida Jalilah Fitria (EKONOMIKA45 : Jurnal Ilmiah Manajemen, Ekonomi Bisnis, Kewirausahaan, 2024)
Research related to "Analysis of the Effect of Job Satisfaction on Turnover Intentions in Teaching Staff at SMA Mekarwangi Lembang". In the S1 Management study program of Digital Technology University.The purpose of this study is to obtain appropriate, trustworthy, and reliable knowledge about the effect of job satisfaction on turnover intentions in teaching staff at SMA Mekarwangi Lembang.This research uses qualitative methods. The result is that job satisfaction positively and significantly affects turnover intentions. That is, the lower the level of job satisfaction obtained, the higher the turnover intention. The conclusion of this study is that there is a significant positive influence between job satisfaction variables and turnover intention variables. This means that the lower the job satisfaction received by the teaching staff and employees at SMA Mekarwangi Lembang, the higher the level of turnover intention from the teaching staff and employees.